Shelf-life Assessment of Tulsi and Stevia Incorporated Low Sugar Kadaknath Egg Jam - Teja, S. V. D.; Nayak, N. K.; Gupta, V. K.; Aich, R.; Dhakad, Reena (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted during from September–January, 2020–2021 in the department of Livestock Products Technology, college of veterinary science and animal husbandry, Mhow, Madhya Pradesh, India. The Kadaknath egg jam was developed to increase nutritional content and decrease sugar content, jam with 1% tulsi and stevia was found suitable and most acceptable by sensory panelists. Hence, selected for further storage stability under refrigeration. TBA, FFA value and microbial count of values for control jam were non-significantly (p<0.05) lower as compared to developed tulsi incorporated low sugar kadaknath egg jam throughout the entire storage. A progressive and significant (p<0.05) increased in the TBA and FFA values of control as well as developed tulsi incorporated kadaknath egg jam observed with advancement of storage. The total plate count (TPC) followed a steadily significantly (p<0.05) increasing pattern from 0–15 day in control as well as developed tulsi incorporated low sugar kadaknath egg jam. Psychrotropic counts as well as Yeast and Mold count were not detected on 10 and 15 day of storage respectively in both control and as well as developed tulsi incorporated low sugar kadaknath egg jam. Coliform were not detected during the entire period of storage in both control as well as developed tulsi incorporated low sugar kadaknath egg jam. The observation indicated that microbial count and rancidity level as well as sensory attributes remained well below the permissible level and product was stable up to 15 days of storage under refrigeration (4±1oC).